ANALISIS PROSES EKSTERNALISASI, OBJEKTIVASI, INTERNALISASI DAN MAKNA SIMBOLIK UPACARA ADAT KARO SUKU TENGGER - Nia Hariwiyanti; I Nyoman Ruja (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
Karo Traditional Ceremony is one of the traditional ceremonies symbolized by the origin of human birth, so that the Karo traditional ceremony is legally obligatory to Tengger Tribe. The objective of study is to analyze the processes of externalization, objectivation, and internalization in the social construction of traditional Karo ceremony Tengger tribe and the meaning of symbols in the Karo traditional ceremony in Ngadisari Village, Probolinggo Regency. This research used a descriptive qualitative method, with a case study approach. Informants of study were the village apparatuses and the heads of Tengger tribal families in Ngadisari village, Probolinggo Regency. Data collection techniques used were interview, observation, and documentation. The results of study indicated that Karo traditional ceremony plays an important role in establishing and maintaining social relations. Social construction in the implementation of Karo traditional ceremony takes place in three processes. It started with the externalization stage, in which parents undertake a process of influencing their descendants. Next is the objectivation stage, in which the community's contribution can be seen from the process of organizing Karo traditional ceremony. The last stage is internalization, in which the Tenggerese people begin to believe in and preserve Karo traditional ceremonial ritual. In a series of processions the Karo Traditional ceremony has the meaning of symbols in a series of events that make the Tengger people tolerant, and obey values ​​and norms applying. The implication of research is that Karo traditional ceremony represents public awareness as indigenous people and can be known widely, especially to the younger generation, so that it can be preserved.